Pemanfaatan Media Pembelajaran Bahasa Arab Berbasis Teknologi terhadap Minat Belajar Peserta Didik - Ahmad Hadi Setiawan; Atika Nur Hidayati (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2024)
This research focuses on the use of learning media used in schools for educators, especially class III SDIT Insan Mulia. This research aims to determine the use of learning media in the learning process, determine the learning interest of students in Class III SDIT Insan Mulia, and find out the obstacles experienced by educators when using technology-based media in the learning process. This research method is qualitative with descriptive data analysis. The data source involved 3 classroom educators, 1 Arabic language teacher and 1 school principal, with research instruments namely interview guides and observations. This data analysis technique uses data reduction, data presentation and drawing conclusions. The results of this research conclude that the presence of technology-based learning media in the learning process at SDIT Insan Mulia increases students' interest in learning based on indicators of learning interest. By using technology-based learning media, Arabic is easier to convey and creates a fun learning atmosphere for educators and students. The obstacles experienced when using learning media in the learning process are that there are still many educators in conducting learning who have not utilized technology-based learning media, there are still students who come in and out of the classroom during the learning process, the infrastructure that supports its implementation is not evenly distributed, the unpreparedness of human resources to utilize the media in the learning process